Strategy for coordinating near-term PM 2.5 , ozone, and CO 2 mitigation in China - Yuxi Liu; Yixuan Zheng; Guannan Geng; Jing Cheng; Yang Liu; Dan Tong; Kebin He; Qiang Zhang (Proceedings of the National Academy of Sciences, 2025)
China faces the challenge of simultaneously improving fine particulate matter (PM 2.5 ) and ozone (O 3 ) air quality while tackling climate change. However, most studies have focused on either the cocontrol of PM 2.5 and O 3 or the synergy between CO 2 reduction and PM 2.5 improvement, leaving comprehensive strategies for tackling all three underexplored. Here, we evaluate various combinations of clean-air and climate policies in China using an integrated framework that consists of a technology-based emission projection model, a goal-oriented measure selection and optimization method, a chemical transport model, and a detailed cost–benefit assessment approach. Our results show that while maintaining current clean-air policies is effective in controlling PM 2.5 , their impact on O 3 remains limited. Maximizing cost-effective end-of-pipe measures targeting NO x and volatile organic compounds can achieve cocontrol of PM 2.5 and O 3 , but remain vulnerable to unfavorable meteorological conditions. Near-term climate policies alone contribute limited improvements in air quality, particularly for O 3 , due to the lower synergy between CO 2 and O 3 precursor emission sources. Only a combined strategy, integrating stringent clean-air actions and ambitious climate mitigation, can achieve the “triple control” of PM 2.5 , O 3 , and CO 2 . Under this strategy, national annual mean PM 2.5 and national O 3 -8 h 90th percentile concentrations are reduced to 19.1 μg m −3 and 126.9 μg m −3 by 2030, respectively, yielding net benefits of over 3,000 billion RMB. Our findings can inform China’s next phase of environmental policies and emission control strategies in developing regions.